La disfuncionalidad familiar y su incidencia en los problemas de lecto-escritura de los alumnos del quinto A y B de educación básica de la escuela Nueve de Julio del cantón Cayambe de la provincia de Pichincha. Año lectivo 2012-2013 - Torres Garcia, Ruth Veronica (2013)
The present paper titled: THE FAMILY DYSFUNCTIONALITY ITS IMPACT ON LITERACY PROBLEMS OF STUDENTS OF THE FIFTH "A" AND "B" BASIC EDUCATION SCHOOL "NINE OF JULY" CAYAMBE CANTON OF THE PROVINCE OF PICHINCHA. ACADEMIC YEAR 2012-2013, I conducted according to the provisions of the Academic Regulations of which is current. The general objective is thus enunciated: To sensitize teachers and parents about the importance of family environment for students of fifth degree of school, promote literacy as a learning process and effective motivator. The methodology included the following methods: Scientist, Analytical-Synthetic; Inductive-Deductive, Descriptive; Statistical Model. As research techniques were applied: The Family Functioning Questionnaire (FF-SIL) to Parents of Students Fifth Grade "A" and "B" General Basic Education School "Nueve de Julio" to establish the Family Dysfunctionality and, a survey applied to Fifth Grade Student "A" and "B" General Basic Education School "Nueve de Julio" to collect information about the Literacy Problems. According to the Family Functioning Questionnaire (FF-SIL), the result is 54 points, states that Fifth Grade Student "A" and "B" Basic General Education School "Nueve de Julio" are located within Family of Moderately Functional range, which is an intermediate expression between functional family dysfunctional family. With the application of the Test of Lecto escritura that you/they were applied the Students of the Fifth Grade "TO" and "B" of Education Basic General of the School "Nine of Julio" to determine the problems of the reading and writing, 56% has a valuation of Good; and 44% reaches a qualification of Regulating. With what is determined that the lecto escritura is not giving good results.